PASINDEN: AWAL KEHADIRANNYA DALAM PERTUNJUKAN WAYANG GOLEK - Sudarsono, Tarjo (LP2M ISBI Bandung, 2018)
In 1930 Sinden became part of the Wayang Golek show. This phenomenon is the creativity of the puppeteer Baraja who was not satisfied with the conventional wayang gol k performance. Finally Sinden presented songs that was entertainment in Wayang Golek show performances. Furthermore, the other puppeteers imitated him and in the end the sind n and the puppeteers became a unity called the